THE HORIZON OF PREDICTION FOR EXCHANGE RATE EUR-LEU - DUMITRU CIOBANU (Annals of the University of Petrosani: Economics)
For the chaotic systems, the fact that they are deterministic does not make them predictable. However, the predictive power in the case of chaotic systems can be improved and this can be illustrated by weather system for which predictions for short periods have reached to a very good accuracy. A positive Largest Lyapunov Exponent indicates the presence of chaos in the evolution of a time series and it is used to establish a correct horizon of prediction.